Thrombophlebia and Pregnancy, Predicting Perinatal Complications and Optimizing Administration Tactics - Bakhodirovna, Khafizova Dilnoza (International Journal of Culture and Modernity, 2022)
Women with a predisposition to thrombosis (with thrombophilia) develop abnormal hypercoagulation during pregnancy, which can lead to early and late reproductive losses. The most significant polymorphisms of thrombophilia genes include antithrombin III deficiency, protein C, Leiden mutation, hereditary hyperhomocysteinemia, and mutations of some other clotting factors. In addition, there is a group of thrombophiliacaused by hyperaggregation. Currently, heparin and its derivatives are considered the safest and most effective drugs for the prevention and treatment of thrombotic complications. However, it is impossible to evaluate the effectiveness of heparins using only standard methods for studying hemostasis (activated partial thromboplastin time, thrombin time, prothrombin time) and markers of intravascular coagulation activation (soluble fibrin monomer complexes, D-dimer) due to their insufficient sensitivity. One of the new tests for qualitative and quantitative assessment of the coagulation state of plasma, which can detect even minimal shifts in the equilibrium of the coagulation system, is considered to be the study of thrombodynamics. Goal. To evaluate the feasibility of using the thrombodynamics test in women with pregnancy pathology in the first trimester. To prove the possibility of its application as the most sensitive method of monitoring therapy with low-molecular-weight heparins (LMWH). Methods. The study included 23 pregnant women with obstetric and gynecological pathology and / or a history of thrombotic complications and the risk of termination of pregnancy in the first trimester. The women were aged 22-38 years (median 30 years). An integral assessment of the hemostatic system was performed using the thrombodynamicstest. Results. LMWH therapy under the control of thrombodynamicswas performed in 20 out of 23 women. As a result, only thrombodynamic parameters were statistically significantly changed (p < 0.05). In 14 women, pregnancy ended with delivery of healthy children at 38-40weeks. (all patients in the first trimester received LMWH). Conclusion. The thrombodynamic test is the most reliable method for monitoring the treatment of LMWH, since it allows you to record even minimal shifts in the balance of the coagulation system. Changes in the hemostatic system occur in a variety of physiological and pathological conditions. Such a physiological process for a woman's body as pregnancy is accompanied by a shift in the balance of hemostasis towards hypercoagulation, which is considered a natural reaction of the body to the expected physiological blood loss during childbirth and in the postpartum period. This is manifested by activation of clotting, mainly due to an increase in the level of clotting factors, a decrease in the activity of protein S and simultaneously a decrease in the activity of fibrinolysis, due to a significant increase in the inhibitor of plasminogen activator types 1 and 2 (PAI-1 and PAI-2) [1-3]. Thrombophilia is a hereditary or acquired predisposition to thrombosis. It should be noted that thrombophilia — this is only a predisposition, but not a disease as such. Usually, thrombophilia becomes clinically significant in the presence of risk factors (cancer, oral contraceptive use, pregnancy, the postpartum period, etc.) [4]. It is customary to distinguish between hereditary and acquired thrombophilia. The most common form of acquired thrombophilia is antiphospholipid syndrome. Another form of acquired thrombophilia may be caused by HIV. In this case, both the disease itself (HIV infection) and antiviral pharmacotherapy contribute to the development of thrombosis [5]. In hereditary thrombophilia, the predisposition to the formation of blood clots is due to genetic mutations. This article will focus mainly on hereditary thrombophilia in pregnant women, the possibilities of anticoagulant therapy, methods of coagulological control and correction of therapy. Carriage of thrombophilia gene polymorphisms can increase hypercoagulation during pregnancy and cause complications. Thrombophilia, according to the literature, has a high degree of correlation with pregnancy complications: spontaneous abortions, habitual miscarriagesuturing, placental abruption, non-developing pregnancy, preterm birth, intrauterine growth retardation, preeclampsia [6-9].